The Intimacy Factor - Catarina Saruga; Alexandre Duarte (Mediapolis)
In an era where traditional advertising loses credibility, individuals seek to know what their favorite media personas are experiencing. Parasocial relationships thrive in this digital landscape, fostering connections without physical proximity. This phenomenon is notably evident in podcasting, where audiences forge intimate connections with hosts. Having realized this, everyday more marketeers are now choosing this medium to advertise their brands throughout. The influence that parasocial relationships have on podcast ads is a complex interplay where fostering connections and potential consumer manipulation meet. Understanding how and why individuals trust podcast hosts when it comes to their consumer behavior is an advantage point to any brand.